Peningkatan Hasil Belajar Mahasiswa Melalui Integrasi IoT dalam Pembelajaran Berbasis Pengalaman pada Pendidikan Tinggi: Penelitian - Pajar Machmud; Akhmad Gunawan; Agus Purwanto; Herianto Saputra (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Digital transformation in higher education demands more contextual and technology-based learning. One key technology from Industry 4.0 that has the potential to be adopted in education is the Internet of Things (IoT). However, IoT implementation in learning systems is still limited, and curricula tend not to accommodate industry needs for graduates with digital literacy and data-driven skills. Students often lack direct experience in applying technology in real-world settings, especially in sustainability and operational efficiency. This research developed a project-based learning model using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) approach integrated with simple IoT devices. Students were tasked with mapping the logistics processes of Small and Medium Enterprises (SMEs), identifying waste sources, and formulating circular supply chain solutions based on data from temperature, humidity, and motion sensors. The projects were conducted collaboratively with SME partners to ensure relevant and applicable learning contexts. The learning process was combined with Kolb's experiential learning cycle to strengthen student engagement and reflection on industry practices. Evaluation showed that 92% of students understood the concept of a circular supply chain, and 85% could operate IoT devices independently. The average final project score reached 93.8/100, with solutions directly valued by the partner SMEs. This research contributes to developing a contextual, technology-based learning model that bridges the academic world and the needs of small industries. Other educational institutions can replicate this model to strengthen the integration of digital literacy, sustainability, and industry collaboration.